Diversidade de polistinae e o uso de Polistes versicolor (Hymenoptera: Vespidae) no controle biológico de Ascia monuste orseis (Lepidoptera: Pieridae) - Jacques, Gabriel de Castro (2018)
Social wasps of the subfamily Polistinae play important ecological roles as pollinators and natural predators of other arthropods. Despite many studies, there is still lack of information on the community structure of Polistinae in anthropogenic environments, an important step to identify the ideal species to be used in biological control programs. Ascia monuste orseis is a key pest of common kale (Brassica oleraceae var. acephala) and can cause losses of up to 100% in production, necessitating forms of control of this insect. Social wasps have already been registered preying on this pest, but there is no work on the use of these insects in their biological control. Thus, the objectives of this study were: i) to investigate the fauna of social wasps in two anthropic areas, identifying species with potential to be used in biological control; ii) investigate the efficiency of two sampling methods, active search and attractive traps; iii) investigate the performance of different attractive baits in the capture of social wasps; iv) to record the species of social wasps that forage in a common kale crop, correlating the temperature and time of day to the foraging habits of these wasps; and v) to test the species Polistes versicolor in the biological control of A. monuste orseis, in autumn and winter, a period of better development of common kale. The research was divided in four experiments: 1) Polistinae diversity of the Instituto Federal de Educação, Ciência e Tecnologia de Minas Gerais (IFMG) - Bambuí Campus ; 2) efficiency of different sampling methods to collect wasps at the Campus of the Universidade Federal de Lavras (UFLA); 3) niche overlap and daily pattern of social wasp activity in a common kale crop; 4) translocation of colonies of P. versicolor to artificial shelters to control A. monuste orseis in common kale. 33 species of social wasps were registered in the IFMG - Bambuí Campus, with P. versicolor being the most collected by active search and attractive traps. In the UFLA, 40 species were recorded, Mischocyttarus cassununga being the most collected by active search and species of the genus Agelaia were the most collected by attractive traps. The active search methodology was more efficient and for the first time molasses were used as attractive bait, and it proved to be the most efficient. Polybia ignobilis, Protonectarina sylveirae and Protopolybia sedula were the main species of wasps that forage on common kale crop. Interspecific interactions among wasp species did not affect the coexistence of them, which could lead to a greater control of the insect pests that occur in the crop. There was a greater foraging between 10 and 11 hours, being important to know this data to know when to apply another method of control, thus contributing to Integrated Pest Management. The translocation of colonies of P. versicolor to common kale during cold and drought periods was not effective for the control of the A. monuste orseis population, due to the low forage activity of this social wasp and, consequently, low predation on the target pest. However, an evaluation is required in the hottest and humid periods of the year, since P. versicolor effectively preys different Lepidoptera species.